Analysis of heat transfer characteristics and optimization of U-tube based solar evacuated tube collector system with different flow conditioning inserts. (1st March 2023) - Bhowmik, Mrinal; Muthukumar, P.; Patil, Ajay
Highlights: Different conceptual design is proposed to improve efficiency of U- tube ETC. CFD model of inserted U-tube geometry is proposed. Insert geometry is optimized by parametric investigation. The twisted tape with square hole ETC provides 10% higher thermal efficiency. The omnipresent solar ΔP-ΔTf -ηth trade-off paradox. Abstract: In the present study, the performance of a U-tube based evacuated tube collector (ETC) for a forced circulation system is tested. The collector tilt angle is varied to analyse the optimum tilt angle to get the higher thermal performance of the solar U-tube ETC regardless of the sun's location. Different flow conditioning inserts are introduced, and its feasibility study is accomplished for the ETC in the place of a conventional plain U-tube ETC to obtain higher system performance. Further, a computational fluid dynamics (CFD) based thermal model is developed in Ansys-fluent R14.5 platform and validated with in-house experimental datasets. Based on the developed CFD model, a detailed parametric study is carried out to optimize the model geometry and operating parameters of solar ETC. CFD results revealed that increasing U-tube diameter from 1/8″ to 3/8″ enhances the net temperature gain by about 39%. Consequently, the proposed flow conditioning inserts models showed a better performance with higher net temperature gain and thermal efficiency under the same condition with acceptable pressure drop penalty. Among the different studied geometries, twisted taped with square holes proved to be the most effective design for obtaining a higher thermal efficiency compared to the plain U-tube design. The temperature contour with streamlines and pressure contour for the best flow conditioning model is also discussed. Furthermore, a trade-off study is accomplished to visualize the thermal efficiency in contrast to pressure drop and net temperature gain.